Recent Publications (Quarterly Journal of Economics, 1947)
Recent Publications Get access The Quarterly Journal of Economics, Volume 61, Issue 2, February 1947, Pages 339–341, https://doi.org/10.1093/qje/61.2.339 Published: 01 February 1947